Barbara Hammer’s History Lessons as a documentary utopia - Talarczyk-Gubała, Monika (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2018)
This article is devoted to the third part of Barbara Hammer’s documentary trilogy, History Lessons. The author analyzes and interprets the form and message of this post-queer essay, with the aim of describing its formula in relation to the mockumentary and found-footage film conventions. She goes back to the pioneer of found footage in the history of world cinema, Esfir Shub, and the position of women in production culture. She refers to Hammer’s debut film, Dyketactics (1974), to describe Hammer’s artistic and political tactic, consisting of intercepting images of women, rooted in visual history, and the subversive quotation of these images against the idea and context of the original. Dyketactics in History Lessons is about quoting archival materials from the genres of documentary, popular science and pornography with the aim of writing the history of the lives of lesbians in the US from the period before the Stonewall riots, where there is very little coverage of the story. The falsifying of archival materials through the editing manipulation of imagery and sound paradoxically uncovers not so much the truth about the lives of lesbians, as what seems to be hidden in images created with a completely different aim than telling the herstory of American women of various orientations and races.